1999
DOI: 10.1523/jneurosci.19-09-03337.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Behavior: Modulation of Locomotion by Light in theDrosophila melanogasterLarva Requires Genetically Distinct Visual System Functions

Abstract: The Drosophila larva modulates its pattern of locomotion when exposed to light. Modulation of locomotion can be measured as a reduction in the distance traveled and by a sharp change of direction when the light is turned on. When the light is turned off this change of direction, albeit significantly smaller than when the light is turned on, is still significantly larger than in the absence of light transition. Mutations that disrupt adult phototransduction disrupt a subset of these responses. In larvae carryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 37 publications
4
68
0
Order By: Relevance
“…Because of the limits of the projector's dynamic range, we could not increase the steepness of the gradient without significantly reducing the size of the experimental arena, so we turned to temporal gradients using triangle waveforms to mimic the stimulus received by larvae moving in straight lines on illumination patterns with a steeper linear spatial gradient. In our previous studies of spatial and temporal gradients of temperature (3)(4)(5)(6)(7)(8)(9)14), odor, and carbon dioxide (10, 11), we found that temporal triangle waves evoked the same behavioral responses as linear spatial gradients.…”
Section: Significancementioning
confidence: 65%
See 2 more Smart Citations
“…Because of the limits of the projector's dynamic range, we could not increase the steepness of the gradient without significantly reducing the size of the experimental arena, so we turned to temporal gradients using triangle waveforms to mimic the stimulus received by larvae moving in straight lines on illumination patterns with a steeper linear spatial gradient. In our previous studies of spatial and temporal gradients of temperature (3)(4)(5)(6)(7)(8)(9)14), odor, and carbon dioxide (10, 11), we found that temporal triangle waves evoked the same behavioral responses as linear spatial gradients.…”
Section: Significancementioning
confidence: 65%
“…2C). We presented larvae with a temporal analog of the checkerboard, a temporal squarewave light stimulus (8,16) (17). The temporal square-wave setup also revealed a distinct photosensory behavior: pausing in response to an abrupt decrease in light intensity (cessation of forward movement without initiation of head-sweeps) ( Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The Drosophila larva performs light-oriented behavior using a pair of photoreceptor bundles that attach to each side of the cephalopharyngeal head skeleton of the maggot and constitute the Bolwig's organs (BO; Fig. 6d) (Busto et al 1999). Originally discovered by Niels Bolwig in the closely related house fly (Bolwig 1946), the BOs had at first not been related to the compound eye.…”
Section: Evolutionary History Of the Drosophila Larval Eyesmentioning
confidence: 99%
“…Since species with primitive ommatidium-type larval eyes are known in both Coleoptera and Diptera (Gilbert 1994), one has to conclude that the reduction of accessory cells occurred independently in the lineages leading to Drosophila and Tribolium. It is noteworthy that in both of these groups, the ecology of larvae appears to render vision less important (Busto et al 1999;Park 1934). The reduction may therefore be the result of evolution against costly visual organs.…”
Section: Recapitulated Fusion Of Ancestral Ommatidal Units In the Larmentioning
confidence: 99%